2014
DOI: 10.1128/genomea.00431-14
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome of the Attenuated Sparfloxacin-Resistant Streptococcus agalactiae Strain 138spar

Abstract: Through the selection of resistance to sparfloxacin, an attenuated Streptococcus agalactiae strain, 138spar, was obtained from its virulent parent strain, S. agalactiae 138P. The full genome of S. agalactiae 138spar is 1,838,126 bp. This genome will allow comparative genomics to identify genes associated with virulence, antibiotic resistance, or other characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…An Ion Torrent PGM (Life Technologies, Inc., Carlsbad, CA) was used for sequencing after extracting DNA from stationary-phase cells of GB1 using standard techniques as described by Thijs et al ( 6 ). In total, 1.52 million reads (mean length 265 bases) generated 403 Mb of data (>362 M Q20 bases) in Torrent Suite 4.2.1.…”
Section: Genome Announcementmentioning
confidence: 99%
“…An Ion Torrent PGM (Life Technologies, Inc., Carlsbad, CA) was used for sequencing after extracting DNA from stationary-phase cells of GB1 using standard techniques as described by Thijs et al ( 6 ). In total, 1.52 million reads (mean length 265 bases) generated 403 Mb of data (>362 M Q20 bases) in Torrent Suite 4.2.1.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Representation of the eight genomic islands predicted using the same software by comparing the S. agalactiae GBS85147 strain against the 16 complete genomes of the S. agalactiae species obtained from the NCBI database. From the inner to outer ring (black) we used the genome of S. agalactiae GBS85147 strain as a reference, followed by GC - (purple) and GC + (green) content, the strains of S. agalactiae 09mas018883 [ 35 ], 138P [ 56 ], 138spar [ 57 ], 2603 V/R [ 58 ], A909 [ 59 ], CNCTC10/84 [ 60 ], COH1 [ 61 ], GBS1-NY [ 62 ], GBS2-NM [ 62 ], GBS6 [ 62 ], GD201008-001 [ 32 ], ILRI005 [ 63 ], ILRI112 [ 63 ], NGBS061 [ 64 ], NGBS572 [ 64 ] and SA20-06 [ 65 ] respectively. The last external ring in 4A display the pathogenic islands while the last external ring in 4B display the genomic islands, respectively …”
Section: Insight From the Genome Sequencementioning
confidence: 99%
“…Pridgeon et al successfully generated an attenuated S. agalactiae strain 138spar from tilapia-derived S. agalactiae serotype Ib strain 138P in laboratory using a sparfloxacin resistance strategy; comparative genome analysis indicated that S. agalactiae 138spar had 22 deletions larger than 6 bp and 26 SNVs [ 7 , 9 ]. Although S. agalactiae serotype Ib strain can cause infection and diseases in various fishes and amphibians, there is no report of its pathogenicity to humans, and comparative genome and phylogenetic studies indicate that S. agalactiae serotype Ia and Ib are distantly related [ 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%